MATERNAL GENETIC PROFILE OF SERBIAN AND MONTENEGRIN POPULATIONS FROM SOUTHEASTERN EUROPE - Jelena Šarac; Dubravka Havaš Auguštin; Ene Metspalu; Natalija Novokmet; Saša Missoni; Pavao Rudan (Genetics & Applications, 2017)
Significant mtDNA variation in Southeastern Europe (SEE) reflects the turbulent and complex demographic history of the region, influenced by gene flow from various parts of Eurasia and a long history of intermixing. In this study we present the maternal genetic profile of the Serbian and Montenegrin populations based on the high resolution analysis of 258 mtDNAs, 119 samples from Serbia and 139 samples from Montenegro. Besides the evidence of minor gene flow from distant central/northeastern Asia, the majority of haplogroups place these populations in the broader genetic landscape of Southeastern Europe, close to their neighbors.